Exposomic determinants of immune-mediated diseases: Special focus on type 1 diabetes, celiac disease, asthma, and allergies: The HEDIMED project approach. Issue 3 (8th June 2022) - Laiho, Jutta E.; Laitinen, Olli H.; Malkamäki, Johannes; Puustinen, Leena; Sinkkonen, Aki; Pärkkä, Juha; Hyöty, Heikki; ,
Abstract : The incidence of immune-mediated diseases (IMDs) is increasing rapidly in the developed countries constituting a huge medical, economic, and societal challenge. The exposome plays an important role since genetic factors cannot explain such a rapid change. In the Human Exposomic Determinants of Immune Mediated Diseases (HEDIMED) project, altogether 22 academic and industrial partners join their multidisciplinary forces to identify exposomic determinants that are driving the IMD epidemic. The project is based on a combination of data and biological samples from large clinical cohorts constituting about 350, 000 pregnant women, 30, 000 children prospectively followed from birth, and 7, 000 children from cross-sectional studies. HEDIMED focuses on common chronic IMDs that cause a significant disease burden, including type 1 diabetes, celiac disease, allergy, and asthma. Exposomic disease determinants and the underlying biological pathways will be identified by an exploratory approach using advanced omics and multiplex technologies combined with cutting-edge data mining technologies. Emphasis is put on fetal and childhood exposome since the IMD disease processes start early. Inclusion of several IMDs makes it possible to identify common exposomic determinants for the diseases, thus facilitating the development of widely operating preventive and curative treatments. HEDIMED includes data and samples from birth cohorts and clinical trials that have used exposomic interventions and cell and organ culture models to identify mechanisms of the observed associations. Importantly, HEDIMED generates a toolbox that offers science-based functional tools for key stakeholders to control the IMD epidemic. Altogether, HEDIMED aims at innovations, which become widely exploited in diagnostic, therapeutic, preventive, and health economic approaches.